2018
DOI: 10.1371/journal.pone.0193491
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of HIV-infected versus HIV-non-infected patients treated for drug-resistance tuberculosis: Multicenter cohort study

Abstract: BackgroundThe emergence of resistance to anti-tuberculosis (DR-TB) drugs and the HIV epidemic represent a serious threat for reducing the global burden of TB. Although data on HIV-negative DR-TB treatment outcomes are well published, few data on DR-TB outcomes among HIV co-infected people is available despite the great public health importance.MethodsWe retrospectively reported and compared the DR-TB treatment outcomes of HIV-positive and HIV-negative patients treated with an individualized regimen based on WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Significantly increased risks of an unfavorable outcome to second-line anti-tuberculosis treatment among HIV-infected versus HIV-uninfected patients were revealed for some patient groups (i.e., 1.22 times higher in mixed-age patients and 1.47 times higher in the eastern region of SSA, compared to their respective counterparts), but the increases in rest of the subgroups were not significant. Consistently, reports of previous studies involving mixed-age patients indicated that older HIV-infected patients had 1.53 [64] and 4.8 [49] times higher hazards of unfavorable outcomes than those older HIV-uninfected. Again, pediatric and elderly individuals were among the mixed-age patients in whom immune statuses might not be competent compared with that of adults/adolescents counterparts.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Significantly increased risks of an unfavorable outcome to second-line anti-tuberculosis treatment among HIV-infected versus HIV-uninfected patients were revealed for some patient groups (i.e., 1.22 times higher in mixed-age patients and 1.47 times higher in the eastern region of SSA, compared to their respective counterparts), but the increases in rest of the subgroups were not significant. Consistently, reports of previous studies involving mixed-age patients indicated that older HIV-infected patients had 1.53 [64] and 4.8 [49] times higher hazards of unfavorable outcomes than those older HIV-uninfected. Again, pediatric and elderly individuals were among the mixed-age patients in whom immune statuses might not be competent compared with that of adults/adolescents counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…A non-significant decrease in the pooled risk of loss from treatment estimated was 0.82 times lower in HIV-infected patients than in those HIV-uninfected. In agreement to this finding, study reports indicated 11.8% versus 26.2% (P<0.001) and 14.2% versus 35.2% rates of loss to follow-up among the HIV-infected versus HIV-uninfected patients; and the loss to follow-up was 7.67 (95% CI: 1.00-59.0) times more likely in the HIV-uninfected patients than in those HIV-infected [80][81][82]. Also, reminding information via cell phone as a part of the HIV/TB integrated program enabled tracing lost patients and resulted in twice more likely returnee for traced patients than untracked ones [83].…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies reported that HIV and DR-TB were the risk factors for each other [ 39 41 , 47 ]. However, this study found no association between HIV-positive and DR-TB patients among TB patients in Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…However, these reviews focus on MDR/RR-TB indicators with limited or no discussion of how MDR/RR-TB treatment affects HIV disease. Despite the extra challenges that HIV co-infection adds to MDR/RR-TB treatment, some studies have shown similar MDR/RR-TB treatment success rates among HIV-positive and HIV-negative MDR/RR-TB patients when ART is available [ 10 , 11 ]. As HIV disease management requires lifelong ART extending well beyond MDR/RR-TB cure, examining how MDR/RR-TB treatment affects HIV disease, its treatment, and its progression is crucial [ 3 ].…”
Section: Introductionmentioning
confidence: 99%